Vertigo shimochii Kuroda & Amano 1960 synonymized with Gastrocopta servilis (Gould, 1843) based on conchological and DNA sequence data - Nekola, Jeffrey C.; Jones, Alex; Martinez, Gabe; Martinez, Sarah; Mondragon, Khayman; Lebeck, Terrence; Slapcinsky, John; Chiba, Satoshi (Zootaxa, 2012)
Kuroda (1960) noted that his new species, Vertigo shimochii Kuroda & Amano, 1960, was distinct from other members of the genus in Japan by possessing a “relatively large and long shell with deep suture and much inflated whorls” (p. 77). While shell shape was noted to be similar to a Gastrocopta, they assigned the species to Vertigo based on its “shell color and lamella characteristics” (p. 77). Vertigo shimochii has since been considered endemic to the southern parts of Japan (The Environment Agency 1988; Minato 1988; Azuma 1995; Biodiversity Center of Japan 2002), and of near threatened status in the Kagoshima Prefecture Red Data Book (Kagoshima Prefectural Government 2003).